MILP Models for Scheduling Dynamic Jobs with Sequence Dependent Setup Times and a Variable Maintenance on a Single Machine - Costa Antonio; Corsini Roberto; Cappadonna F. Antonio; Fichera Sergio (Journal of Advances in Applied & Computational Mathematics, 2018)
The single machine scheduling problem with variable maintenance has been widely investigated by both academics and practitioners. Differently from most papers proposed so far, and conforming to a real-world process in the semiconductor industry, in this paper a single variable maintenance task has to be carried out within a specific time interval. The maintenance duration is an increasing function of its starting time. The objective is to minimize the total tardiness considering release times and sequence dependent setup times of jobs as well. Since an earlier maintenance starting time implies a smaller maintenance duration but a higher completion time of the subsequent jobs, the best schedule including maintenance activity and jobs has to be achieved. In order to optimally solve the scheduling problem at hand, two distinct mixed integers linear programming models (MILPs) are proposed and compared under the computational efficiency viewpoint.